Citizen Arrest in Iranian, British and US Laws - Kazemi, Seyyed Sajjad; Heidari, Sajjad (International Journal of Psychosocial Rehabilitation, 2020)
Citizen participation and a sense of responsibility can help criminal justice activists, including law enforcement officers and officials, discover the crime and arrest the perpetrator. Citizen Arrest Authority, for the first time, in the Criminal Procedure Code of 2013 under Article 45 has become objectified in Note 1. From the historical point of view, the origin of this institution can be traced back to English law, starting from the medieval and until now the regulations on it have been developed and completed. The most important basis for arresting citizen in Iranian law can be regarded as the issue of to promote virtue and prevent vice. In the United States, too, there is a high degree of social participation in criminal justice and, in other words, the rule of participatory criminal policy, as the main basis for citizen arrest. In all three penal regimes, Iran, the United Kingdom and the United States have the same degree of citizen with some differences; first, the crime must be of the type of crime that requires immediate intervention and prompt action. Second, there is a necessity and a reasonable reason for citizen involvement, for example, the lack of a judicial officer can justify the necessity. Third, the offense was committed or is being committed; therefore, it is not possible for citizens to intervene before committing a crime. Of course, there are differences in the scope of citizen intervention in these three legal systems, including: In Iran, the most serious crimes, in the United States the most obvious crimes and crimes, in the United Kingdom, are punishable by two-fold crime, ranging from citizen intervention to crime detection and arrest.